2021
DOI: 10.3390/brainsci11091169
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Two Methods (Inside-Out/Outside-In) Inferior Articular Process Resection for Uniportal Full Endoscopic Posterolateral Transforaminal Lumbar Interbody Fusion: Technical Note

Abstract: Objective: There is limited literature comparing the uniportal full endoscopic posterolateral transforaminal lumbar interbody fusion outside-in approach (ETLIF (O)) with the inside-out approach (ETLIF (I)). Methods: Radiological evaluation was performed on disc height restoration and coronal wedging angle, and operation time (inferior articular process resection time/total operation time) and clinical evaluation were made. Result: 48 cases of inside-out and 38 cases of outside-in cases were included. Compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
(72 reference statements)
0
9
0
Order By: Relevance
“…endoscopic fusion using a larger diameter uniportal stenosis endoscope. There was no fusion data and muscle cross-sectional area evaluation in these studies [12][13][14]. We found that there was sustained improvement in pain and function with VAS, ODI, and MacNab's criteria in this study while the complications were minor with no implant-related revision or adjacent segment disease at 2 years after index operation.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…endoscopic fusion using a larger diameter uniportal stenosis endoscope. There was no fusion data and muscle cross-sectional area evaluation in these studies [12][13][14]. We found that there was sustained improvement in pain and function with VAS, ODI, and MacNab's criteria in this study while the complications were minor with no implant-related revision or adjacent segment disease at 2 years after index operation.…”
Section: Discussionmentioning
confidence: 57%
“…EPTLIF is an alternative posterolateral approach to the traditional Trans-Kambin approach in uniportal endoscopic fusion and was used in this cohort study. It was previously described by Kim et al [ 12 , 13 , 18 ] and Wu et al [ 14 , 19 ]. Surgery was performed on a Wilson Frame over a radiolucent table, and the patient was under general anesthesia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…17,46 3) Uniportal full endoscopic posterolateral route transforaminal interbody fusion using a similar approach to biportal endoscopic interbody fusion, the facets were resected and harvested as bone graft and a large interbody cage was inserted after disc preparation with the aid of large stenosis endoscope. 19,20,22 The advantage of endoscopic fusion with full facet resection is that large interbody cage can better stabilize the anterior column of lumbar spine as a load sharing device, this helps to promote fusion and prevents implants failure due to reversed bending movement generated if there is insu cient anterior column support. 47 In our Endo-TLIF cohort we used the technique of uniportal full endoscopic posterolateral route transforaminal interbody fusion which allowed large cages used in MIS-TLIF to be inserted in our patients who underwent Endo-TLIF.…”
Section: Discussionmentioning
confidence: 99%
“…Soft tissue dissection done with radiofrequency ablator, isthmus and inferior articular process is exposed and bony drilling is done on the isthmus and inferior articular process for inferior articular facetectomy which is harvested as bone graft. 22 Superior articular facet is drilled under endoscopic guidance and harvested as bone graft. We subsequently remove ligamentum avum and expose the ipsilateral disc space and the traversing and exiting nerve root.…”
Section: Description Of Technique Uniportal Full Endoscopic Posterola...mentioning
confidence: 99%